Highlighting multicomponent reactions as an efficient and facile alternative route in the chemical synthesis of organic-based molecules: a tremendous growth in the past 5 years - Mohlala, Reagan Lehlogonolo; Rashamuse, Thompho Jason; Coyanis, Elena Mabel (Frontiers in Chemistry, 2024)
Since Strecker's discovery of multicomponent reactions (MCRs) in 1850, the strategy of applying MCRs approach have been in use for over a century. Due to their ability to quickly develop molecular diversity and structural complexity of interest, MCRs are considered as efficient approach in organic synthesis. Although MCRs such the Ugi, Passerini, Biginelli, and Hantzsch are widely studied, this review emphasizes the significance of selective MCRs to elegantly produce organic compounds of potential use in medicinal chemistry, industrial and material science applications, as well as the use of MCRs approach to sustainable methods. During synthesis MCRs provide advantages such atom economy, recyclable catalysts, moderate conditions, preventing waste, and avoiding solvent use. MCRs also reduce the number of sequential multiple reactions to one step.